Durvalumab, with or without tremelimumab, plus platinum–etoposide versus platinum–etoposide alone in first-line treatment of extensive-stage small-cell lung cancer (CASPIAN): updated results from a randomised, controlled, open-label, phase 3 trial. Issue 1 (January 2021) - Goldman, Jonathan W; Dvorkin, Mikhail; Chen, Yuanbin; Reinmuth, Niels; Hotta, Katsuyuki; Trukhin, Dmytro; Statsenko, Galina; Hochmair, Maximilian J; Özgüroğlu, Mustafa; Ji, Jun Ho; Garassino, Marina Chiara; Voitko, Oleksandr; et al.
Summary: Background: First-line durvalumab plus etoposide with either cisplatin or carboplatin (platinum–etoposide) showed a significant improvement in overall survival versus platinum–etoposide alone in patients with extensive-stage small-cell lung cancer (ES-SCLC) in the CASPIAN study. Here we report updated results, including the primary analysis for overall survival with durvalumab plus tremelimumab plus platinum–etoposide versus platinum–etoposide alone. Methods: CASPIAN is an ongoing, open-label, sponsor-blind, randomised, controlled phase 3 trial at 209 cancer treatment centres in 23 countries worldwide. Eligible patients were aged 18 years or older (20 years in Japan) and had treatment-naive, histologically or cytologically documented ES-SCLC, with a WHO performance status of 0 or 1. Patients were randomly assigned (1:1:1) in blocks of six, stratified by planned platinum, using an interactive voice-response or web-response system to receive intravenous durvalumab plus tremelimumab plus platinum–etoposide, durvalumab plus platinum–etoposide, or platinum–etoposide alone. In all groups, patients received etoposide 80–100 mg/m 2 on days 1–3 of each cycle with investigator's choice of either carboplatin area under the curve 5–6 mg/mL/min or cisplatin 75–80 mg/m 2 on day 1 of each cycle. Patients in the platinum–etoposide group received up to six cycles of platinum–etoposide every 3 weeks and optional prophylactic cranial irradiation (investigator's discretion). Patients in the immunotherapy groups received four cycles of platinum–etoposide plus durvalumab 1500 mg with or without tremelimumab 75 mg every 3 weeks followed by maintenance durvalumab 1500 mg every 4 weeks. The two primary endpoints were overall survival for durvalumab plus platinum–etoposide versus platinum–etoposide and for durvalumab plus tremelimumab plus platinum–etoposide versus platinum–etoposide in the intention-to-treat population. Safety was assessed in all patients who received at least one dose of study treatment. This study is registered at ClinicalTrials.gov, NCT03043872 . Findings: Between March 27, 2017, and May 29, 2018, 972 patients were screened and 805 were randomly assigned (268 to durvalumab plus tremelimumab plus platinum–etoposide, 268 to durvalumab plus platinum–etoposide, and 269 to platinum–etoposide). As of Jan 27, 2020, the median follow-up was 25·1 months (IQR 22·3–27·9). Durvalumab plus tremelimumab plus platinum–etoposide was not associated with a significant improvement in overall survival versus platinum–etoposide (hazard ratio [HR] 0·82 [95% CI 0·68–1·00]; p=0·045); median overall survival was 10·4 months (95% CI 9·6–12·0) versus 10·5 months (9·3–11·2). Durvalumab plus platinum–etoposide showed sustained improvement in overall survival versus platinum–etoposide (HR 0·75 [95% CI 0·62–0·91]; nominal p=0·0032); median overall survival was 12·9 months (95% CI 11·3–14·7) versus 10·5 months (9·3–11·2). The most common any-cause grade 3 or worse adverse events were neutropenia (85 [32%] of 266 patients in the durvalumab plus tremelimumab plus platinum–etoposide group, 64 [24%] of 265 patients in the durvalumab plus platinum–etoposide group, and 88 [33%] of 266 patients in the platinum–etoposide group) and anaemia (34 [13%], 24 [9%], and 48 [18%]). Any-cause serious adverse events were reported in 121 (45%) patients in the durvalumab plus tremelimumab plus platinum–etoposide group, 85 (32%) in the durvalumab plus platinum–etoposide group, and 97 (36%) in the platinum–etoposide group. Treatment-related deaths occurred in 12 (5%) patients in the durvalumab plus tremelimumab plus platinum–etoposide group (death, febrile neutropenia, and pulmonary embolism [n=2 each]; enterocolitis, general physical health deterioration and multiple organ dysfunction syndrome, pneumonia, pneumonitis and hepatitis, respiratory failure, and sudden death [n=1 each]), six (2%) patients in the durvalumab plus platinum–etoposide group (cardiac arrest, dehydration, hepatotoxicity, interstitial lung disease, pancytopenia, and sepsis [n=1 each]), and two (1%) in the platinum–etoposide group (pancytopenia and thrombocytopenia [n=1 each]). Interpretation: First-line durvalumab plus platinum–etoposide showed sustained overall survival improvement versus platinum–etoposide but the addition of tremelimumab to durvalumab plus platinum–etoposide did not significantly improve outcomes versus platinum–etoposide. These results support the use of durvalumab plus platinum–etoposide as a new standard of care for the first-line treatment of ES-SCLC. Funding: AstraZeneca.